HLA-DR expression as a biomarker of inflammation for multicenter clinical trials of ocular surface disease - Epstein, Seth P.; Gadaria-Rathod, Neha; Wei, Yi; Maguire, Maureen G.; Asbell, Penny A. (Experimental eye research, 2013)
There are currently no validated minimally invasive objective metrics for the classification and evaluation of ocular surface diseases and/or for evaluating treatment efficacy. We thus sought to establish a standardized methodology for determining the relative amount of the inflammatory biomarker HLA-DR on the ocular surface and to evaluate the precision, reliability and repeatability of its use for large multicenter clinical trials and translational research studies of ocular surface disease. Multiple studies were conducted to establish a Standard Operating Procedure (SOP) for utilizing HLA-DR expression as a minimally invasive, objective, ocular surface inflammatory biomarker. The established SOPs provide specific guidelines for HLA-DR collection and analysis, in order to incorporate it reliably into multicenter clinical trials and/or translational research. Duplicate cell samples from impression cytology (IC) samples of both normal and dry eye individuals were collected and split to assess repeatability (between the splits and between the duplicate samples). To determine storage capability, one duplicate was stained immediately and the other after 30 days cold storage. To demonstrate the feasibility of the use of the SOP for a multicenter clinical trial, clinicians out-of-state were trained to collect IC samples, and the samples shipped to our Biomarker Laboratory, logged, processed and analyzed. Demonstration of the ability to incorporate of IC into a randomized double masked clinical trial of dry eye disease (DED) was performed. In all cases, processing and analyses were performed by a masked independent observer. The validity/viability of the SOPs was established by demonstrating that: 1) sufficient numbers of cells can be collected via IC; 2) the precision/repeatability of the relative biomarker expression quantified in samples; 3) personnel at distant sites can be taught to collect, store and ship samples successfully; 4) samples can be stored for up to 30 days (refrigeration) before processing without affecting results; 5) IC can be incorporated into a double blind randomized clinical trial (RCT) of DED; and 6) the Biomarker Laboratory can track a large number of masked samples reliably. In conclusion, our standard operating procedure for impression cytology analysis of HLA-DR expression appears to be repeatable and reproducible for use in multicenter clinical trials, providing a minimally invasive objective biomarker of inflammation of the ocular surface. •SOP valid. Similar areas of subject yields similar results. Use for other markers.•Storing for up to 30 days does not have significant effect on HLA-DR detection.•Other sites taught to collect samples. Successful incorporation in clinical trial.•Data supports HLA-DR as biomarker for DED severity and degree of inflammation.•Our SOPs demonstrate technique reliable, usable in multicenter clinical trials.